1996
DOI: 10.3354/meps138309
|View full text |Cite
|
Sign up to set email alerts
|

Growth production of the euphausiid Nyctiphanes simplex on the coastal shelf off Bahía Magdalena, Baja California Sur, México

Abstract: ABSTRACT. Growth production of the euphausiid Nyctiphanes sirnplex Hansen was examined off the southwest coast of the peninsula of Baja California, Mexico (Bahia Magdalena, 24 to 25" N ) , as a function of seasonal changes of temperature, zooplankton biomass, upwelling index, and regional ocean circulation. The data were collected during 4 oceanographic surveys from June to November 1986. High densities of N. sirnplex were found in the shallow coastal waters (c300 m). High production is maintained during late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 7 publications
1
16
1
Order By: Relevance
“…These latitudinal trends are reasonably constant unlike the diel variability observed in the SSLs appearance caused by the 24-h vertical migration reported by Robinson and Gómez-Gutiérrez (1998). Latitudinal changes in N. simplex growth production was reported by Gómez-Gutiérrez et al (1996), supporting the idea that the southern region is less productive than northern ones, and the SSLs are less dense and smaller along the southern part of Baja California. Estimations of the standing stock expressed as the carbon content of three of the most abundant euphausiid species indicate that the northern area is at least four times more productive than the southern area, showing different productivity between these two environments.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These latitudinal trends are reasonably constant unlike the diel variability observed in the SSLs appearance caused by the 24-h vertical migration reported by Robinson and Gómez-Gutiérrez (1998). Latitudinal changes in N. simplex growth production was reported by Gómez-Gutiérrez et al (1996), supporting the idea that the southern region is less productive than northern ones, and the SSLs are less dense and smaller along the southern part of Baja California. Estimations of the standing stock expressed as the carbon content of three of the most abundant euphausiid species indicate that the northern area is at least four times more productive than the southern area, showing different productivity between these two environments.…”
Section: Discussionsupporting
confidence: 56%
“…Along the west coast of Baja California, a strong latitudinal environmental gradient occurs during autumn (Gómez-Gutiérrez et al, 1996, Gómez-Gutiérrez andRobinson, 1997). Because it is known that zooplankton assemblages have latitudinal changes along Baja California during this season (i. e. Brinton, 1962Brinton, , 1979Gómez-Gutiérrez et al, 1995, Gómez-Gutiérrez andRobinson, 1997), an interesting comparative study can be performed of the aggregation behavior of the SSLs of temperate and tropical epipelagic assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…All previous information about Nyctiphanes simplex biomass productivity, and therefore its vital rates, was deduced from preserved specimens (Lavaniegos 1995, Gómez-Gutiérrez et al 1996, De Silva-Dávila & Palomares-García 1998, De SilvaDávila et al 2002. The same approach was used to estimate biomass production for the other 3 Nyctiphanes species around the world (Lindley 1982, Ritz & Hosie 1982, Hosie & Ritz 1983, Barange & Stuart 1991.…”
Section: Vital Ratesmentioning
confidence: 99%
“…Multiple studies have estimated Nyctiphanes simplex biomass production rates along the west coast of Baja California peninsula (Lavaniegos 1995, Gómez-Gutiérrez et al 1996, De Silva-Dávila et al 2002 and in La Paz Bay (southwestern Gulf of California; De Silva-Dávila & Palomares-García 1998). However, all these studies estimated N. simplex productivity using only preserved specimens without any direct measurements of vital rates.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to our expec-tations, when we used a submarine video camera, a scientific echosounder, and a zooplankton net in this present study, we discovered that dense epibenthic swarms of adult N. simplex commonly enter through a relatively shallow (28 to 50 m depth) section of the main mouth of this subtropical bay. Gómez-Gutiérrez (1995) and Gómez-Gutiérrez et al (1996) reported that the abundance, population structure, and secondary production of Nyctiphanes simplex over the continental shelf of Bahía Magdalena demonstrates the formation of dense swarm densities in spring and summer (average 1075 and 2520 ind. ) when the water column is warmer, well mixed, and contains low phytoplankton concentration because of the retreat of the CC toward the north.…”
Section: Introductionmentioning
confidence: 99%